AI-Driven Marketing Strategies: Assessing the Impact of Artificial Intelligence in Transforming Sustainable Marketing Practices for MSMEs a Qualitative Study - Candra Aeni; Loso Judijanto; Encep Sopandi; Subhanjaya Angga Atmaja; Dewi Maharani (Global Research Collaboration, 2026)
This study aims to analyze how AI contributes to the transformation of sustainable marketing practices among MSMEs, with particular attention to its implementation, benefits, challenges, and adoption strategies. A descriptive qualitative method was used in this investigation. Ten informants participated in in-depth interviews and observations to gather primary data. From five stakeholder groups: MSME owners/managers, business practitioners, AI developers, digital marketing and sustainability experts, and consumers. Secondary data were obtained from academic literature, journal articles, policy documents, and other relevant publications. Data reduction, data display, and conclusion drawing were used to examine the data, with source and technique triangulation providing support. The findings reveal that AI enhances sustainable marketing by improving marketing automation, customer personalisation, and data-driven strategic decision-making. MSME owners and business practitioners reported that AI reduced marketing operational costs and increased customer engagement through more targeted communication. AI developers and sustainability experts emphasized that AI supports efficient resource utilization and digital marketing processes, contributing to reduced environmental impacts. However, high implementation costs, limited digital competencies among MSMEs, and worries about the security and privacy of consumer data continue to be significant obstacles to the deployment of AI. AI has considerable potential to strengthen sustainable marketing practices and improve MSME competitiveness. To maximize its benefits, more inclusive adoption strategies are needed, including affordable SaaS-based AI solutions, digital capacity-building programs for MSMEs, and supportive regulatory frameworks that encourage ethical and responsible AI implementation.